Discrepancy between two-dimensional and three-dimensional digital subtraction angiography for the planning of endovascular coiling of small cerebral aneurysms <5 mm. Issue 6 (December 2020) - Wu, Te-Chang; Tsui, Yu-Kun; Chen, Tai-Yuan; Ko, Ching-Chung; Lin, Chien-Jen; Chen, Jeon-Hor; Lin, Ching-Po
Background: To investigate the discrepancy between two-dimensional digital subtraction angiography and three-dimensional rotational angiography for small (<5 mm) cerebral aneurysms and the impact on decision making among neuro-interventional experts as evaluated by online questionnaire. Materials and methods: Eight small (<5 mm) ruptured aneurysms were visually identified in 16 image sets in either two-dimensional or three-dimensional format for placement in a questionnaire for 11 invited neuro-interventionalists. For each set, two questions were posed: Question 1: "Which of the following is the preferred treatment choice: simple coiling, balloon remodeling or stent assisted coiling?"; Question 2: "Is it achievable to secure the aneurysm with pure simple coiling?" The discrepancies of angio-architecture parameters and treatment choices between two-dimensional-digital subtraction angiography and three-dimensional rotational angiography were evaluated. Results: In all eight cases, the neck images via three-dimensional rotational angiography were larger than two-dimensional-digital subtraction angiography with a mean difference of 0.95 mm. All eight cases analyzed with three-dimensional rotational angiography, but only one case with two-dimensional-digital subtraction angiography were classified as wide-neck aneurysms with dome-to-neck ratio < 1.5. The treatment choices based on the two-dimensional or three-dimensional information were different in 56 of 88 (63.6%) paired answers. Simple coiling was the preferred choice in 66 (75%) and 26 (29.6%) answers based on two-dimensional and three-dimensional information, respectively. Three types of angio-architecture with a narrow gap between the aneurysm sidewall and parent artery were proposed as an explanation for neck overestimation with three-dimensional rotational angiography. Conclusions: Aneurysm neck overestimation with three-dimensional rotational angiography predisposed neuro-interventionalists to more complex treatment techniques. Additional two-dimensional information is crucial for endovascular treatment planning for small cerebral aneurysms.